Pengukuran Antropometri Balita dan Perempuan Usia Subur Pasca Bencana Erupsi Gunung Sinabung di Desa Pertenguhen Kecamatan Simpang Empat Kabupaten Karo - Nadya Ulfa Tanjung; Sri Wahyuni (FKM UIN Sumatera Utara Medan, 2021)
Indonesia is a country that is very prone to natural disasters. Nutritional problems that usually arise in natural disasters are malnutrition in the age group of infants and toddlers who do not get breast milk (ASI) because the child is separated from his mother when a natural disaster occurs. The worsening nutritional status of a group of people due to frequent delays in food aid and limited food availability in evacuation sites can exacerbate existing conditions. Nutrition problem is essentially a public health problem, however, the prevention cannot be done with a medical approach and health services. The cause of the emergence of nutritional problems is multi-factor, therefore the tackling approach involves various related sectors. Emergency nutrition management during a disaster becomes the first priority where food and nutrition services are an integral part of emergency management. Nutrition counseling provided by nutrition officers during a disaster emergency has significant meaning. Extension is an effort to change human behavior, both individuals and society so that it can create mental attitudes and the ability to solve problems it faces in order to improve and maintain good nutrition. The hope of this effort is that people can understand the importance of food and nutrition, so that they are willing to behave and act according to nutritional norms.